Prevalent factors affecting the proliferation of coffee shops in Iloilo City - Barrido, Frene; Conadera, John Paul; Desabelle, Eba May; Espinosa, Krystle Joy; Porol, Esperanza
This study aimed to identify the prevalent factors affecting the proliferation of coffee shops in Iloilo City. Customer profile, customer preference and area feasibility factors were considered as key determinants of the proliferation. The respondents of the study were the 94 customers of the 10 different coffee shops in Iloilo city. These coffee shops are Bluejay's specialty Coffee & Delicatessen; Bo's Coffeeshop; Coffeebreak; Coffee Dream; Coffee Plus; Crammer's Cafe; Dulgies Coffee & Desserts; Espresso Centrale; Oxen's Cafe; and JJV coffeeshop. For its independent variables, the following factors were included under the customer profile: sex, age, civil status, educational attainment, school, and weekly allowance/income. Under the customer preference, the frequency of avaling the different products and services by the customers and their reasons for such choices were assessed. The frequency of visits, duration of stay and time of the day are also independent variables. area feasibility factors were also considered. Proliferation of the coffee shops is the dependent variable. This study utilized a validated researcher-made questionnaires to gather the needed data; one questionnaire for the customer and another one for the management. The data was computed using the Package for Social Sciences (SPSS) software. To describe the data gathered, the mean, mode and standard deviation were used. Different establishments in the Gen. Luna St., where there are a number of coffee shops, were also taken into account. The findings of the study as to the customer's profile, majority of the respondnets belong to the following categories: female; 21-25 years old; single; student; bachelor's degree; private school; weekly allowance of Php501-Php1,000 and; income below Php 500 and above Php15,000. As to the customer preference, the following obtained the highest mean: iced coffee (coffee preparation), mocha (coffee blend), shake (non-coffee beverage0, sandwich (other products), study area (services) and location (personal reasons). Most of the establishments near coffee shops belong to the food industry sector.